Oncological Outcome of Oncoplastic Breast Surgery: A Review of the Literature - Najafi, Massoome; Salmon, Remy; Kaviani, Ahmad (Archives of Breast Cancer, 2015)
Oncoplastic breast surgery (OBS) has gained widespread acceptance during the last two decades as an integral component of breast cancer surgery. OBS combines oncological principles of breast cancer surgery with plastic surgery techniques to provide the best cosmetic results without compromising oncological outcome of breast cancer treatment and it has opened up the possibility to perform breast conservation in large tumors. The purpose of this review is assessment of the oncological outcome of OBS in the treatment of breast cancer. We performed an extensive search of PubMed for articles published on oncological results and safety of OBS. There are few randomized clinical trials (RCTs) comparing the results of OBS with standard breast conservation techniques; however, based on the results of several prospective studies, it can be concluded that in terms of oncological outcome, OBS is at least as safe as standard techniques for breast conservation.